An observational study on the influence of latissimus dorsi length on upper limb reaction time in recreational volleyball players - Pinto, Royline Fathima; Binu, Sreelakshmi M.; K. B., Riyas Basheer (International Journal of Research in Medical Sciences, 2025)
Background: Reaction time is a critical determinant of athletic performance, particularly in sports like volleyball that demand rapid upper limb responses. The latissimus dorsi muscle, essential for upper limb mobility and postural stability, may influence neuromuscular responsiveness through its length and flexibility. This observational study aimed to investigate the relationship between latissimus dorsi muscle length and upper limb reaction time in recreational volleyball players aged 18-25 years. Methods: Eighty recreational volleyball players aged 18-25 years were recruited. Participants with a normal lumbar lordotic angle and disabilities of the arm, shoulder, and hand (DASH) scores indicating no significant upper limb disability were included. Lumbar lordosis was assessed using the flexicurve method, latissimus dorsi muscle length was measured using an inch tape, and upper limb reaction time was evaluated via the ruler drop test. Data were analyzed using SPSS version 23.0, with Spearman’s correlation employed to assess associations. Results: A weak positive correlation was observed between right latissimus dorsi length and right upper limb reaction time (r=0.222, p<0.05), while a moderate positive correlation was found between left latissimus dorsi length and left reaction time (r=0.313, p<0.05). These findings suggest that increased muscle length is associated with slightly prolonged reaction times. Conclusions: This study found a significant weak-to-moderate positive correlation between latissimus dorsi length and upper limb reaction time. These results suggest that muscle flexibility may influence neuromuscular performance and highlight the need for further research into flexibility training to enhance athletic performance.